EFEKTIVITAS KERJA OPERATOR TOWING CARMELALUIPENENTUAN WAKTU BAKU - Noor Syamsu Hidayat; Irfan Setiawan; Rohana Sitanggang (Institut Transportasi dan Logistik Trisakti, 2015)
Akebono Astra Indonesia Jakarta (AAIJ) is a manufacturing company with major product brake for vehicle wheels 2 and 4 as a main product. In distributing goods in plant 1, this company use material handling equipment such as towing car. Problems encountered is the lack of accurate measurement of working time although it has added rating factor and allowances. Because of the time in the field, car towing operator work time longer than the company expected. One way of measuring standard time (working time has been added rating factor and allowances) is the stopwatch method (clock stop). The purpose of writing is to know the amount of the actual car towing cycle time and standard time, how the elements of the work and standardizing the order of elements of the work and effectiveness of the towing car to the period of 2014. From this study, it is expected the company can improve operator effectiveness towing car